CLINICAL UTILITY OF ROTATIONAL THROMBOELASTOMETRY IN DETECTING HEMOSTATIC DISORDERS - Sabljić, Nikica; Mitrović, Mirjana (Medicinski podmladak, 2020)
Hemostasis represents an equilibrium between procoagulant and anticoagulant processes, but once this balance is shifted to one side, it leads to coagulopathy presented by pathological bleeding or thrombosis. Many conditions could cause coagulopathy. The most common are sepsis, severe traumas and malignancies. Widely used conventional coagulation tests (CCTs), focused only on clot initiation, are primary used to detect hypocoagulability. Viscoelastographic tests (VET), like rotational thromboelastometry (ROTEM) are whole blood tests, can detect problems in different stages of coagulation, from initiation thought clot elongation and propagation, to the clot lysis and might reveal both, hypercoagulability and hypocoagulability. ROTEM have gained popularity in the care of patients with TIC, as tool to guide transfusion support. Nowadays it is widely used in other medical specialties, too. Several studies in septic patients pointed out hypocoagulable ROTEM pattern as a predictor of poor prognosis. Additionally, there is great interest of ROTEM usage in malignancies, although limited research is currently available, it suggests ROTEM have ability to identify a patient in high risk of thrombosis. Further investigations trough randomized studies are needed to confirm ROTEM utility and to help in making a consensus about its use in different medical occasions.
Keywords: coagulopathy, rotational thromboelastometry, sepsis, trauma induced coagulopathy, malignancies